Prospective analysis of the role of actors in governing mangrove ecosystem area in Tangerang District, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mahardika SMAH, Yulianda F, Adrianto L, Sulistiono. 2022. Prospective analysis of the role of actors in governing mangrove ecosystem area in Tangerang District, Indonesia. Biodiversitas 23: 4940-4947. The role of actors in the governance of mangrove ecosystems is one of the main factors in determining the sustainability of mangrove ecosystem management in the Tangerang District, Banten, Indonesia. The research aims to analyze actors' prospective role in the strategy of governance of mangrove ecosystems areas in Tangerang using the MACTOR method. This research is a descriptive case study with an expert judgment approach. The study results show that the central and local governments have an important role in the governance strategy of mangrove ecosystem areas in the Tangerang. The two actors can collaborate with the local community, the private sector, universities, NGOs, research institutions, and high schools. The strategy for the governance of mangrove ecosystems in Tangerang can be done by increasing the role of each actor by encouraging the central government and local governments to implement programs to achieve the most supportive strategic goals, namely the management of mangrove ecosystems based on collaborative management (co-management). The strategy can be easily implemented and get more optimal results by involving the role of the user community, NGOs, universities, local governments, and research institutions where the level of collaboration (convergence) is high to support the strategy.